2019
DOI: 10.1177/2192568219889362
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Computed Tomography and Spine Surgery: A Narrative Review

Abstract: Study Design: Narrative review. Objective: This article seeks to provide a narrative review regarding the ability of opportunistic information available from computed tomography (CT) scans to guide decisions in spine surgery related to patient bone quality. Methods: A review of the literature (limited to human and English language) was performed via PubMed and Google Scholar using the search terms; “osteoporosis” AND “opportunistic” AND “computed tomography” AND “spine surgery.” The titles and then abstracts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…1 BCT is reported to provide opportunistic measure of bone density as well as bone strength based on finite element analysis performed on a clinical CT scan. 2 While there are studies correlating BCT results to fracture risk, there are currently no studies correlating BCT results to outcomes of spinal reconstructive surgery. Additionally, there are currently no studies showing the application of BCT in guiding treatment for patients undergoing spinal reconstructive surgery.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…1 BCT is reported to provide opportunistic measure of bone density as well as bone strength based on finite element analysis performed on a clinical CT scan. 2 While there are studies correlating BCT results to fracture risk, there are currently no studies correlating BCT results to outcomes of spinal reconstructive surgery. Additionally, there are currently no studies showing the application of BCT in guiding treatment for patients undergoing spinal reconstructive surgery.…”
Section: To the Editormentioning
confidence: 99%
“…egarding the recent article ''Best Practice Guidelines for Assessment & Management of Osteoporosis in Adult Patients Undergoing Elective Spinal Reconstruction, 1 spine surgeons may be interested in information not covered in this article concerning an accurate clinical test for diagnosing osteoporosis that is well suited for spinalfusion patients. 2 Given the well-known limitations of dual-energy X-ray absorptiometry (DXA) testing at the spine that are associated with degenerative changes for spinal fusion patients, 3,4 and the weak correlation between T-scores from hip DXA and spine DXA, 5 the guidelines discussed possibly using noncalibrated Hounsfield Unit measurements from an existing computed tomography (CT) scan to assess osteoporosis. While this ''opportunistic'' approach is attractive since it exploits the availability of an already-taken CT scan, that method is investigational, unstandardized, does not account for different scan acquisition settings, and, as noted in the guidelines, is not approved for diagnostic purposes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Demir et al [4] also found that the Hounsfield unit (HU) values of the vertebrae in stabilized segments consistently decreased postoperatively. Patients with low BMD are at risk of complications such as vertebral compression fractures, cage subsidence, and screw loosening [5][6][7]. Therefore, accurate measurement of vertebral BMD is important in patients who have undergone instrumented spinal fusion for the timely diagnosis of osteoporosis and provision of medical treatment.…”
Section: Introductionmentioning
confidence: 99%